Strategies and Efforts to Increase Children's Interest in Reading in Gampong Mamplam - Bukhari; Rahmi , Mutia; Ainun; Azzuhra, Wilda; Ananda, Siska; Anwar; Habeahan , Soufi Sakinah; Yani, Salwa Sahpija; Pebrina, Maghfirah; Karmila, Susi; Rahmayani, Rahmayani; Fachrurrazi; Syawila , Zuhrayana; Quthni , Afhdar; Maisy Alpha, Moch. Bahril (MEUSEURAYA - Jurnal Pengabdian Masyarakat, 2023)
The purpose of this study is to find alternatives to increase interest in reading among children, as an effort to overcome low interest in reading. Good reading interest is an indicator of literacy progress as well as an indicator of the nation's progress. The steps taken in this service are by having a mini library filled with interesting story books where every 5 days a week before starting the activity there is a reading together. This strategy is created and implemented by students with the aim of increasing reading interest in children in Mamplam village, with frequent reading every day makes children accustomed to reading activities. These strategies and efforts show the result that having a mini library is able to develop an interest in reading in children in Gampong Mamplam, which becomes a change in the children and makes them more enthusiastic about reading.